Analisis Kinerja Keuangan Bank BUMN Dengan Metode RGEC Financial Performance Analysis of BUMN Banks Using The RGEC Method - Ratna Gumilang, Risa; Nuryana, Nuryana (Coopetition : Jurnal Ilmiah Manajemen, 2025)
Indonesia's economy has experienced a contraction, which can impact all aspects of the country's economy and pose challenges to the sustainability of the banking business. The banking sector plays a crucial role in economic recovery by providing credit to individuals or entrepreneurs in need of working capital. This study aims to assess the financial performance and health condition of BUMN banks using the RGEC method. The research employs a qualitative descriptive approach. The secondary data used consists of financial reports of BUMN banks from 2019 to 2023, obtained from the Indonesia Stock Exchange website and the respective banks' official websites. The findings indicate that Bank Mandiri has the lowest average NPL compared to other BUMN banks. Bank Mandiri ranks first in GCG implementation, while BRI, BNI, and BTN share the second position. Bank BRI has the highest average ROA and CAR among BUMN banks. The health condition of BUMN banks based on the RGEC method over the past five years shows that Bank BRI and Bank Mandiri are in a "Highly Healthy" condition, while Bank BNI and BTN are classified as "Healthy”.